From Confrontation to Collaboration: Peasant Negotiations in the Arena of Decentralization - Amin Tohari (Department of Political Sciences, Faculty of Social and Political Sciences, UIN Sunan Ampel Surabaya, 2021)
Decentralization and local democracy are two inseparable elements of post-New Order Indonesia development politics. Furthermore, the quality of decentralization to a certain extent is influenced by the depth and quality of local democratic practices. This study reveals that decentralization is not only an arena of competition between local elites in possession of capital through local democratic institutions, but also an arena in which grassroots groups (peasants) could fight for their land rights. This study observes that local democratic procedures and institutions that are practiced in unison with decentralization are not utilized by the lower classes in the struggle for their rights. This shows the failure of local democratic institutions from taking root in the marginal groups. The success of peasant movements in the struggle for their rights and the practice of local elite domination of the decentralization arena does not come out of the blue, but is related to the history of the formation of the agrarian structure and social class. This study concludes that on one side, local elites trust democratic institutions and procedures to achieve their goals, while on the other side the grassroots have their own logic on how local democracy should have been practiced, namely by not separating practice of local democracy from the missions of justice and social welfare for the common good.